Comparison of 2 training programs for basic laparoscopic skills and simulated surgery performance in veterinary students. Issue 8 (9th October 2017) - Chen, Chi‐Ya; Ragle, Claude A.; Lencioni, Rachael; Fransson, Boel A.
Abstract: Objective: To compare the effects of 2 training curricula on laparoscopic skills and performance of simulated surgery in veterinary students. Study design: Prospective study. Sample population: Veterinary students (n = 33) with no prior hands‐on experience in minimally invasive surgery. Methods: Basic laparoscopic skills (BLS) were assessed based on 5 modified McGill inanimate system for training and evaluation of laparoscopic skills. Motion metrics and an objective structured assessment of technical skills (OSATS) were used to evaluate surgical skills during a simulated laparoscopic cholecystectomy performed in an augmented reality simulator. Students were randomly assigned to either skill‐based (group A) or procedural‐based (group B) training curriculum. Both tests were performed prior to and after a 10‐session training curriculum. Results: Post‐training BLS results were improved in both training groups ( P < .001). Seven participants completed both presimulated and postsimulated laparoscopic cholecystectomy, preventing paired analysis. Based on motion metrics analysis, participants completed tasks in a shorter time ( P = .0187), and with better economy of movement ( P = .0457) after training. No difference was detected in OSATS before and after training. Conclusion: Both training curricula improved BLS, but significant differences were not detected between the procedural‐based training program and basic skills training alone in veterinary students. Motion metrics such as time, economy of movement, and instrument path were superior to an OSATS, when assessing surgical performance. Further studies are needed to compare the effects of different simulators on the training of veterinarians with diverse laparoscopic surgical experience.